Фармакогностичне дослідження Бедринця ломикаменевого (Pimpinella saxifraga) - Паращук, Е. А.; Parashchuk, E. A. (Запорізький державний медичний університет, Тернопільський національний медичний університет імені І. Я. Горбачевського, 2020)
Дисертаційна робота присвячена вивченню цінної лікарської рослини з родини селерові (Apiaceae) бедринцю ломикаменевого (Pimpinella saxifraga L.). Проведено комплексний фармакогностичний аналіз трави та кореневищ і коренів досліджуваної рослини. У сировині бедринцю ломикаменевого встановлена наявність аміно- та гідроксикоричних кислот, полісахаридів, флавоноїдів, кумаринів, дубильних речовин, жирних і органічних кислот, сапонінів, ефірної олії, визначено їх кількісний вміст. У надземних і підземних органах рослини визначено елементний склад. Методом ВЕРХ у траві бедринцю ломикаменевого ідентифіковано 17 зв’язаних і 15 вільних амінокислот; у кореневищах і коренях – 17 зв’язаних і 13 вільних амінокислот. У траві переважають за вмістом такі вільні амінокислоти як пролін (1,60 мкг/мг) і глутамінова кислота (1,34 мкг/мг) не виявлено незамінної амінокислоти метіоніну та замінної цистину. Із зв’язаних амінокислот домінують глутамінова кислота (174,03 мкг/мг) і цистин (144,05 мкг/мг). У кореневищах і коренях бедринцю ломикаменевого з вільних амінокислот найбільший вміст аргініну (4,23 мкг/мг) і не виявлено гістидину, цистину, лізину і метіоніну. Зі зв’язаних амінокислот у підземних органах бедринцю ломикаменевого домінують глутамінова кислота (10,20 мкг/мг) і цистин (11,96 мкг/мг). Зі зв’язаних амінокислот у надземних і підземних органах бедринцю ломикаменевого кількісно переважають глутамінова кислота і цистин. The thesis is devoted to the study of a valuable medicinal plant called burnet saxifrage (Pimpinella saxifraga L.) from the family of celery (Apiaceae). A complex pharmacognostic analysis of the herb and the rhizomes with roots of the studied plant was carried out. Amino acids, hydroxycinnamic acids, polysaccharides, flavonoids, coumarins, tannins, fatty and organic acids, saponins, essential oil were found in the burnet saxifrage raw material, and their quantitative content was determined. The elemental composition of the above-ground and underground organs of the plant was determined. By means of the HPLC method, 17 bound and 15 free amino acids were identified in the herb of burnet saxifrage; 17 bound and 13 free amino acids were found in the rhizomes and roots. In the herb, such free amino acids as proline (1.60 μg/mg) and glutamic acid (1.34 μg/mg) prevail by content, though no methionine as an essential amino acid and cystine as a non-essential one were identified. As regards the bound amino acids, glutamic acid (174.03 μg/mg) and cystine (144.05 μg/mg) predominate. In the rhizomes and roots of burnet saxifrage, arginine (4.23 μg/mg) has the highest content among all free amino acids, though no histidine, cystine, lysine and methionine were detected. As for the bound amino acids, glutamic acid (10.20 μg/mg) and cystine (11.96 μg/mg) predominate in the underground organs of burnet saxifrage. Such bound amino acids as glutamic acid and cystine quantitatively dominate in the both above-ground and underground organs of burnet saxifrage. The fractions of water-soluble polysaccharides (WSPS) and pectic substances (PS) were distinguished in the herb, rhizomes and roots of burnet saxifrage, the quantitative content of which was the following: WSPS – herb – 6.95 %, rhizomes and roots – 11.25 %; PS – herb 11.89 %, rhizomes and roots – 4.41 %. The GC/MS method determined the monomer composition of polysaccharides of the studied plant. The composition of polysaccharide complexes of rhizomes and roots revealed 5 sugars, 2 of which were identified; in the herb – 13 sugars, identified – 3. D-glucose and sucrose were identified in both samples of the raw materials. D-fructose with the content of 0.68 mg/kg was also detected in the aboveground organs. The largest amount of sucrose, i.e. 33.96 mg/kg, was found in the underground organs of burnet. The quantitative content of free organic acids in the burnet saxifrage herb and the rhizomes with roots was determined, which constituted 0.37 % and 0.44 %, respectively. The TLC method revealed the presence of oxalic, citric, succinic, benzoic, tartaric and traces of salicylic acids in the burnet saxifrage herb and oxalic, citric, succinic, tartaric – in rhizomes and roots. As for the organic acids, oxalic, malonic, succinic and citric acids were identified in the underground organs of burnet saxifrage by means of the GC/MS method. Levulinic acid was found in the aboveground organs of burnet. The qualitative and quantitative content of fatty acids in the studied burnet saxifrage raw material was determined by means of the GC/MS method. Thus, 12 fatty acids were identified in the herb and 9 fatty acids were found in the underground organs. Polyunsaturated fatty acid – linoleic (5.59 mg/kg and 43.10 mg/kg, respectively) is found to be predominant in the herb and the rhizomes with roots; of the saturated – palmitic (4.05 mg/kg and 7.15 mg/kg, respectively). The lipophilic fraction of the burnet saxifrage herb and the rhizomes with roots was obtained, whose yield was 7.88 % and 5.25 %, respectively.
Pharmacognostic study of burnet saxifrage (Pimpinella saxifraga)
Keywords: бедринець ломикаменевий; трава; кореневища і корені; густий екстракт; фармакогностичне і фармакологічне дослідження; морфолого-анатомічний аналіз; burnet saxifrage; herb; rhizomes and roots; thick extract; pharmacognostic and pharmacological research; morphological and anatomical analysis